Role of the neurotrophic receptor TrkC in the pathogenesis of Trypanosoma cruzi infection. - Weinkauf, Craig. (2017)
Abstract: Chagas' disease is caused by infection with the obligate intracellular parasite Trypanosoma cruzi. Gastrointestinal failure, which results from nerve tissue destruction, is a major complication of Chagas' disease. The neurotrophic receptor TrkA mediates T. cruzi cellular invasion of some neural and non-neural cells, but several infected cell types such as cardiomyocytes and nerve tissue cells in the colon and heart lack TrkA expression. Using in vitro assays we report that TrkC, which shares a common ligand (NT-3) and sequence homology with TrkA, mediates T. cruzi cellular invasion. Under the same conditions, the third Trk family receptor, TrkB, does not mediate cellular invasion. The parasite molecule responsible for binding TrkC is PDNF/TS, as it co-immunoprecipitates with TrkC and also inhibits invasion in TrkC expressing cells. Trk receptors and their neuroprotective signaling underlie the development and maintenance of mammalian nervous tissue. We show that T. cruzi can promote TrkC-dependent cell survival, as it does with TrkA, and that invasion in TrkC- or TrkA-expressing cells results in more robust intracellular parasite division. As such, and even though in vitro cellular invasion leads to cell death due to intracellular parasite overgrowth during the course of 4-7 days, TrkC and TrkA may serve a dual beneficial role for T. cruzi by mediating cellular invasion and simultaneously providing trophic signals that help maintain the parasite's environment. To determine the significance of T. cruzi-Trk interactions in Chagas' disease, we focused on a mouse model of T. cruzi infection. Acute infection in mice was specifically blocked using α-TrkA and α-TrkC antibodies, which suggests both receptors play an important role in mammalian infection. Continuing with this model, as parasites spread from the initial inoculation site, parasitemia peaks 11 days post inoculation (dpi) and colon parasitism peaks at 18 dpi. Focusing on the nerve tissue cells of the colon, which express TrkB and TrkC but not TrkA, we found a roughly 60% reduction of TrkC-expressing cells in infected mice versus uninfected mice, whereas TrkB mRNA remains constant, which suggests TrkB cells are spared. These data raise the possibility that T. cruzi preferential invasion of TrkC-expressing cells results in the destruction of a specific subpopulation of nerve tissue cells in the colon. In addition, TrkC cell death correlates with increased colon size in infected mice. Although megacolon (an enlarged non-functional colon) can occur in Chagas' disease patients, this is the first such evidence showing mice infected with T. cruzi develop enlarged colons. Our data support a novel model of T. cruzi colon pathology such that T. cruzi preferential invasion of TrkC-expressing cells leads to specific destruction of TrkC-expressing cells in the colon, which results in pathological enlargement of the colon. Given the broad expression of TrkC in the PNS and in other highly relevant tissues in Chagas' disease, such as muscle cells of the heart, our data raise the further possibility that TrkC plays a prominent role in mediating invasion and tissue damage in organs other than the colon.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Immunology.; Advisor: Mercio PereiraPerrin.; Committee: Peter Brodeur, Steve Bunnell, Eric Frank, and Ricardo Gazzinelli.; Keywords: Immunology, and Neurosciences.